The Analysis of Current Level of Communication of a Contributory Organization and Proposals for Increasing of its Effectiveness - Ullmannová, Kristýna (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá současnou komunikační strategií Lipky, školského zařízení pro environmentální vzdělávání, a možnostech zlepšení této strategie zvláště s ohledem na oblast zahradního vzdělávání. Teoretická část se zaměřuje na vysvětlení základních konceptů v rámci dané problematiky. Následující část pak představuje výsledky interních a externích analýz komunikační strategie Lipky. Tato část též poukazuje na možné nedostatky a navrhuje alternativní řešení pro vylepšení efektivity komunikace. Práce se zaměřuje na pedagogy z jihomoravského kraje a jejich přehled o aktivitách Lipky a také jejich zájem o nabízené kurzy.

This thesis deals with the current communication strategy of Lipka, school facility for environmental education, and the possibilities of improving such strategy especially with regards to the area of garden education. The theoretical part focuses on presenting the basic concepts within the area of interest. The following part presents the results of both internal and external analysis of Lipka's communication strategy. It also debates possible shortcomings and suggests alternative solutions for improving its efficiency. This thesis is focused on the pedagogues from the South Moravian Region and their knowledge about the activities of Lipka and also their interest in offered courses.
The Analysis of Current Level of Communication of a Contributory Organization and Proposals for Increasing of its Effectiveness
Keywords: Neziskový sektor; propagace; public relations; green care; zahradní vzdělávání; pedagogové; Non-profit sector; promotion; public relations; green care; garden education; pedagogues